SPECIFIC FEATURES OF LINGUACULTURAL UNITS IN ENGLISH AND UZBEK LANGUAGES - Ermuhammadova , Marjona Bobomurod qizi (Innovative Development in Educational Activities, 2024)
this article explores the intricate relationship between language and culture, focusing on specific linguistic features in English and Uzbek languages. It explores how greetings, proverbs, hospitality expressions, ceremonial language, humor, and sarcasm reflect cultural values and norms in each language. Additionally, it examines how communication styles, characterized as high-context in Uzbek culture and low-context in English culture, shape interpersonal interactions. While Uzbek language serves as a repository of cultural identities and fosters collectivism, English facilitates individual expression and global interconnectedness. Understanding these linguistic and cultural dynamics is essential for effective communication across diverse contexts.